INFLUENCE OF ELECTRICAL ENERGY QUALITY ON TECHNOLOGICAL PROCESSES IN LIVESTOCK - Sinyavsky, A.; Savchenko, V. (Енергетика і автоматика, 2016)
The influence of the voltage deviation, voltage unbalance and power outages on production processes in livestock are analyzed. The technological losses component are defined when parameters of power quality are deviating from the nominal value.